Condensed finite element scheme for symmetric multi-layer structures including dilatational motion. (13th October 2022) - Arasan, U.; Sreekumar, A.; Chevillotte, F.; Triantafyllou, S.P.; Chronopoulos, D.; Gourdon, E.
Abstract: Condensed models act as useful tools to reduce the computational time in the finite element simulations by describing the dynamic behaviour of the multi-layer structure with only one equivalent homogeneous layer. Many condensed plate models in the literature assume constant velocity through the thickness which allows only anti-symmetric motions like bending and shear, but do not include symmetric motions like dilatational or compressional behaviour. The recently developed condensed model by Marchetti et al. (2021) overcomes this setback by including the symmetric motion through three dynamic intrinsic parameters of the multi-layer structure: a dynamic bending stiffness and two dynamic mass densities. This paper presents a finite element scheme to compute vibro-acoustic quantities from the condensed layer with these three dynamic parameters. It is further showed that the proposed scheme has high computational gain over the conventional full three-dimensional finite element approach. Highlights: A new FE scheme is proposed to compute vibro-acoustic indicators of symmetric multi-layer structures. The proposed scheme can be applicable to thick as well as thin structures. It offers high computational savings over the conventional 3D FE. The scheme can be applied to multi-layer with solid, fluid or poroelastic layers.